2016
DOI: 10.17236/sat00096
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of coagulation and serum biochemistry profiles in dairy cattle with different degrees of fatty liver

Abstract: The aim of the present study was to investigate clotting profiles, plasma biochemical, and hematological parameters in cows with different degrees of fatty liver. The degree of fatty liver was determined based on histopathology of liver biopsies. Fifty cows referred for left displacement of the abomasum and different degrees of fatty liver were investigated. A clotting profile including prothrombin time (PT), thrombin time (TT), activated partial thromboplastin time (aPTT), and fibrinogen did not reveal differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A further explanation for the lower glucose concentrations can be attributed to the greater demand for milk lactose synthesis, whose concentration was continuously elevated throughout the experiment in H-Chol. (Gerspach et al, 2016;Rehage et al, 1996;Reid & Collins, 1980), but may not necessarily be pathological. In this respect, Petzold et al (2015) refer to a likely enhanced capability…”
Section: Discussionmentioning
confidence: 99%
“…A further explanation for the lower glucose concentrations can be attributed to the greater demand for milk lactose synthesis, whose concentration was continuously elevated throughout the experiment in H-Chol. (Gerspach et al, 2016;Rehage et al, 1996;Reid & Collins, 1980), but may not necessarily be pathological. In this respect, Petzold et al (2015) refer to a likely enhanced capability…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum proteins, such as fibroblast growth factor-21, hemoglobin, and angiopoietin-like protein 4 can be used as fatty liver biomarkers in lactating dairy cows ( Shen et al., 2018 ; Wang et al., 2018 ). Gerspach et al. (2016) found that AST, rather than NEFA, TC, or TG, is a biochemical parameter that distinguishes cows with fatty liver.…”
Section: Discussionmentioning
confidence: 93%